Foundations of meaningful educational assessment (McGraw-Hill Higher Education, 2009)
Contents: The nature of assessment; The psychological foundations of assessment; The social foundations of assessment; Assessment: the link between standards and learning; Selected-response assessments; Constructed-response assessments...